The game as an enabler of learning - Luna Rincon, Erika Constanza; García Calderon, Maria Carolina; Vargas Velásquez, Claudia Patricia (Rastros Rostros, 2002)
The game is a possibility to make children spontaneously be immensely creative, starting from their inner motives. It is a scenario that they build for their self-expression through imagination, speculation, inquiry, and concerns. Therefore, the world in which they live is discovered and learned through play.